2020
DOI: 10.1371/journal.pone.0231439
|View full text |Cite
|
Sign up to set email alerts
|

Baseline factors predicting the need for corneal crosslinking in patients with keratoconus

Abstract: Introduction The primary purpose of crosslinking is to halt the progression of ectasia. We retrospectively assessed the condition of keratoconus patients who were followed-up at least twice after the initial examination to evaluate keratoconus progression, to identify definitive factors to predict a later need for corneal crosslinking (CXL). Methods The medical charts of 158 eyes of 158 keratoconus patients (112 males and 46 females; mean age, 27.8 ± 11.7 years), who were followed up at the Department of Ophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Age is an inevitable factor in keratoconus progression, partly because keratoconus is a disorder that tends to progress depend on the patients’ age; its progression tends to slow during middle age but young onset keratoconus has been shown to progress much faster [ 33 , 34 ]. We had previously investigated the condition of keratoconus patients who were followed-up twice or more after the initial visit and found that the patients’ age was the most relevant factor with respect to keratoconus progression, followed by Rmin (the minimum sagittal curvature evaluated by Pentacam HR) of the corneal frontal plane [ 35 ]. The disproportionate influence of age between progression and non-progression groups was ineluctable.…”
Section: Discussionmentioning
confidence: 99%
“…Age is an inevitable factor in keratoconus progression, partly because keratoconus is a disorder that tends to progress depend on the patients’ age; its progression tends to slow during middle age but young onset keratoconus has been shown to progress much faster [ 33 , 34 ]. We had previously investigated the condition of keratoconus patients who were followed-up twice or more after the initial visit and found that the patients’ age was the most relevant factor with respect to keratoconus progression, followed by Rmin (the minimum sagittal curvature evaluated by Pentacam HR) of the corneal frontal plane [ 35 ]. The disproportionate influence of age between progression and non-progression groups was ineluctable.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, parameters reported to have predictive value in KC progression include young age, 20 , 21 , 22 , 23 low TCT, 24 high Kmean, 24 high anterior Kmax 18 , 23 and posterior Kmax, 25 high central posterior 24 or anterior 20 elevation, index of surface variance (ISV), 26 high index of height decentration (IHD), 26 and vertical coma. 25 The fact that none of the initial corneal tomography parameters had predictive value for progression in this study whereas some initial biomechanical parameters showed significant differences between the groups supports the argument that the primary derangement in KC is biomechanical and that tomographic changes follow biomechanical disruption.…”
Section: Discussionmentioning
confidence: 99%
“…In the age group 1, group 2 and group 3, there were 97, 445 and 342 eyes from 884 patients and the mean age was 15.5±1.5 (10)(11)(12)(13)(14)(15)(16)(17)(18) No difference was found for eye rubbing (RUB), presence of allergies (ALLRG), contact lens use (CL), presence of family member with KC (Family KC), coexistence of thyroid disorders (Thyroid) and presence of Neurodermitis (NRDRM) among age groups. However, there was a difference in some of the aforementioned parameters among progressive and nonprogressive eyes (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A young age below 18 years, is an independent risk factor for progression of KC [3,4,[12][13][14], even though progression may also occur beyond the age of 30 [5,13,15]. Sherman et al reported that in multivariate analysis, age 30 or younger conferred a sevenfold increased risk of transplantation compared with ages of over 40 [13].…”
Section: Discussionmentioning
confidence: 99%